Monsters in the Pacific: The Philippines in the Hollywood Geopolitical Imaginary - Castillo, Laurence Marvin S. (Archīum Ateneo, 2024)
The recent announcement of the American strategic pivot to the Asia Pacific calls for the examination of the ways by which the region, particularly its constituent states, is produced in and by the US imperialist imaginary. This essay responds to such critical imperative by analyzing the geopolitical imagination of the Philippine nation-space in the Hollywood giant monster films Pacific Rim (2013) and Godzilla (2014). The essay first discusses how the nation-state remains a crucial participant in the globalized expansion of capital, and how its participation is imagined in the realm of cinematic geopolitics. It then examines the development of the giant monster genre in relation to postwar geopolitics. Finally, the essay argues that the filmic constructions of the Philippine nation-space in the two films function to allegorize the country’s position within the geopolitical design of American imperialism in the region.